PROSPEK PEMBESARAN IKAN BAWAL (Colossoma macropomum) DI DESA SUKOSARI KECAMATAN BELITANG KABUPATEN OKU TIMUR - Yudi Zuriah (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The purpose of this study is to: (1) To find out how much the cost of production and acceptance of the enlargement of pomfret (Colossoma macropomum) in one production process, (2) To find out how the value of the feasibility of enlargement of bawal fish (Colossoma macropomum) in one time production process. This research was conducted in Sukosari Village, Belitang District, OKU Timur Regency. Determination of research location is done purposively or purposely, with the consideration that in Sukosari Village is one of the villages that develop bawal fish enlargement farming and the area has enough population in the research criteria. The study was conducted in February 2015 until it was completed. This study found that the average cost of revenues and revenues of pomfret fish breeding in the production period of 4 months, obtained revenue in pomfret breeding business amounted to Rp 37.322.467 / process, while the income from the business of raising fish pomfret Rp 11.352.433 / process. The analysis of R / C ratio obtained from the enlargement of pomfret fish in 4 months is 1.4, which means that every one rupiah sacrificed will be obtained by the receipt of 1.4 so the enlargement of pomfret is said to be profitable. ROI analysis represents the rate of return on capital where ROI on the business of fish bawal enlargement is 42%.